Biostimulants derived from organic urban wastes and biomasses: An innovative approach - Giordana, Alessia; Malandrino, Mery; Zambon, Alfonso; Lusvardi, Gigliola; Operti, Lorenza; Cerrato, Giuseppina (Frontiers in Chemistry, 2023)
We used humic and fluvic acids extracted from digestate to formulate nanohybrids with potential application in agronomy. In order to obtain a synergic co-release of plant-beneficial agents we functionalized with humic substances two inorganic matrixes: hydroxyapatite (Ca₁₀(PO₄)₆(OH)₂, HAp) and silica (SiO₂) nanoparticles (NPs). The former is a potential controlled release fertilizer of P and the latter has a beneficial effect on soil and plants. SiO2 NPs are obtained by a reproducible and fast procedure from rice husk, but their ability to absorb humic substances resulted very limited. HAp NPs coated with fulvic acid are instead a very promising candidate, based on desorption and dilution kinetic studies. The different dissolution kinetics observed for HAp NPs coated with fulvic and humic acids could be related to the different interaction mechanism, as suggested by FT-IR study.